Synthesis of 2-alkylamino-4-methylquinoline-6-r’-phenylsulfamides and their antimicrobial activity - Oleksiyenko, T. O.; Grytsenko, I. S.; Osolodchenko, T. P. (Zaporozhye Medical Journal, 2013)
Series of new 2-alkylamino-4-methylquinoline-6-phenylsulfamides was obtained by the reaction of 2-chloro-4-methylquinoline-6-phenylsulfamides with appropriate aliphatic amines in conditions of microwave radiation and their physical and chemical characteristics were studied. The results of microbiological screening revealed that the synthesized compounds showed high activity against Gram-positive microorganisms and C. albicans, but revealed less active effect against gram-negative microorganisms. Some «structure-activity» relationships have been found.